Quantitative nodal burden as a predictive marker for chemotherapy benefit in postoperative ampullary adenocarcinoma: a multi-institution population-based study - Li, Zheng; Sun, Chongyuan; Li, Zefeng; Fei, He; Xing, Cheng; Zhao, Dongbing (Frontiers in Immunology, 2025)
BackgroundThe effectiveness of adjuvant chemotherapy (ACT) in ampullary adenocarcinoma (AA) patients and under what conditions ACT should be applied are not clearly defined.MethodsThe study encompassed a series of consecutive AA patients who underwent curative surgical resection. These patients were sourced from the National Cancer Center of China, spanning the years 1998 to 2020, as well as from 12 registries within the Western surveillance, epidemiology, and end results program, covering the period from 2004 to 2017. The quantitative nodal burden was evaluated using the log odds of positive lymph nodes (LODDS). The correlation between ACT and overall survival (OS), recurrence-free survival (RFS), and cancer-specific survival (CSS), was meticulously evaluated using Cox proportional hazards regression models and tested by interaction analysis.ResultsDespite its rarity, a total of 948 and 225 eligible patients were included in the Western cohort and the China cohort, respectively. ACT was not significantly associated with improved long-term survival of unselected AA patients in both the China cohort (OS: P = 0.86, RFS: P = 0.84) and Western cohort (OS: P = 0.11, CSS: P = 0.82). After the quantitative analysis of nodal tumor burden, the study revealed that in patient subgroup with LODDS exceeding -1.4, significantly prolonged survival outcome emerged in patients received ACT (Surgery+ACT VS. Surgery alone, HR: 0.38, 95% CI: 0.19 - 0.75, P = 0.01). The multivariate analysis demonstrated that increasing LODDS was associated with increasing survival benefit from ACT (P for interaction = 0.03), whereas the N classification did not reliably identify patients benefiting from ACT based on statistical test of interaction (P = 0.20).ConclusionThis study emphasizes the potential of LODDS to inform personalized therapeutic decisions in the management of AA.